Spatiotemporal Variation of the Meteorological and Groundwater Droughts in Central Taiwan - Yeh, Hsin-Fu (Frontiers in Water, 2021)
In recent years, Taiwan has been facing severe water shortage because of extreme weather. In addition, changes in rainfall patterns resulted in an increasingly notable drought phenomenon, which affects the management and utilization of water resources. Therefore, the basins in Central Taiwan were used as study sites in this study. Long-term records from 13 rainfall and 17 groundwater stations were selected. The Standardized Precipitation Index (SPI) and Standardized Groundwater Level Index (SGI) were used to analyze the drought characteristics of this region. The rainfall and groundwater level data from basins in Central Taiwan were analyzed in this study. The results show that the year 2015 was a year with severe drought and has some correlation with SPI and SGI signals. In addition, with regards to groundwater drought, more drought events occurred in the Da'an River basin, but the drought duration and intensity were relatively low, in contrast to that in the Wu River basin. Finally, the correlation between SPI and SGI was analyzed in this study. The correlation between SPI and SGI varies in different basins, but a certain degree of correlation was observed in all basins. The results show that the drought intensity is relatively higher when the drought duration is longer. With regards to severe droughts, droughts caused by rainfall occur at a higher frequency than those caused by groundwater.